Information Characteristics and Errors in Expectations: Experimental Evidence. (8th March 2017) - Antoniou, Constantinos; Harrison, Glenn W.; Lau, Morten I.; Read, Daniel
Abstract : We design an experiment to test the hypothesis that, in violation of Bayes' rule, some people respond more forcefully to the strength of information than to its weight. We provide incentives to motivate effort, use naturally occurring information, and control for risk attitude. We find that the strength–weight bias affects expectations but that its magnitude is significantly lower than originally reported. Controls for nonlinear utility further reduce the bias. Our results suggest that incentive compatibility and controls for risk attitude considerably affect inferences on errors in expectations.